Vozes que decolonizam o saber: narrativas insurgentes de mulheres do Pantanal Sul sob o olhar dos estudos culturais - TAYNARA MARTINS DE MORAES (2021)
This dissertation was born from observations made over the past few years about the representation of the Pantanal image in the media and how this process violently influenced the exclusion of Pantanal womens from the canon built about the region, preventing them from occupying their spaces as representatives of cultural diversity, both in digital media and in physical resources. Making use of the interdisciplinarity provided by the qualitative-exploratory method, we began our dialogue firstly through a bibliographical survey, in which we collated authors from Cultural and Decolonial Studies such as Gayatri Spivak (2010), Néstor Garcia Canclini (2013), Stuart Hall (2014), Maria Lugones (2008), Edward P. Thompson (1981; 1998), Aníbal Quijano (2005), Oyéronké Oyewùmi (2017), among others. In the second act, we conducted a field survey, through a semi-structured interview, in which four Pantanal women who exercise/exercised distinct activities in the Southern Pantanal region participated. With this, our goal was founded on listening to the voice of Pantanal women as a potential decolonial path against the hegemony attached to the Pantanal lands by the discourses that carry the dominant ideologies of the colonizer, that were being built by these subjects about a different relationship with this Pantanal, interpreted through their experiences and resistance. We set ourselves up to listen to these voices, to listen to alterity, so as to allow the opening of a more diverse and human construction of the Southern Pantanal, from the resignification of her knowledge and actions, constituent and representative of this territory.